PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR KECAMATAN KONGBENG KABUPATEN KUTAI TIMUR - Sulau Ipung (ADMINISTRASI PUBLIK, 2019)
This research is motivated by the leadership function of Kongbeng sub-district employee motivation in increasing employee work productivity.The purpose of this study was to find out how the motivation of employees at the Kongbeng Office. The type of research or explanation used is descriptive quantitative used to analyze the relationship between research variables. The type of data used is questionnaire, observation, interview, and documentation.From the results of the study it was found that work motivation with employee work productivity is very positive, this can be proven by calculating the determination of R2 obtained by 0.770 or 77% and 23% influenced by other factors. From the hypothesis test t test results obtained t count is greater than t table, where 3.475> 1.699.